Preliminary perception of teaching and learning using Telegram social media tool / Mohammad Nizam Ibrahim … [et al.] - Ibrahim, Mohammad Nizam (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2016)
The purpose of this study was to investigate the perception of students’ using ‘Telegram’ as a support tool for teaching and learning. The population of this study was 66 students who were studying Bachelor of Electrical and Electronic Engineering at Universiti Teknologi MARA, Pulau Pinang. The students were exposed to the Telegram application as a supporting tool in their teaching and learning during Mac – September 2015 academic semester. At the end of the semester, an online survey consisting of a true-false question, several agreement-level questions and open-ended questions were developed using google form that was distributed to students via the Telegram application to collect their feedbacks. The student feedbacks were analysed to obtain results on their perception. The results indicated that the Telegram tool does support student learning process in term of easily sharing information and interaction with lecturers and their classmates. The obtained results could be used to motivate lecturers to employ the Telegram tool for supporting teaching and learning process.